Emerione A, a novel fungal metabolite as an inhibitor of New Delhi metallo-β-lactamase 1, restores carbapenem susceptibility in carbapenem-resistant isolates. (March 2022) - He, Yan; Zhou, Shupeng; Sun, Weiguang; Li, Qin; Wang, Jianping; Zhang, Jinwen
Highlights: The fungal secondary metabolites emerione A and asperfunolone A have potential NMD-1 inhibitory activity. Emerione A had significant activity in cells (Kd  = 11.8 ± 0.6 μM; IC50  = 12.1 ± 0.9 μM) against NDM-1-producing bacteria. The structure of asperfunolone A was elucidated via extensive spectroscopic analyses and X-ray crystallography. NDM-1-producing E. coli strains could be resensitised to meropenem with emerione A and asperfunolone A. After treatment with emerione A, K. pneumoniae ATCC BAA-2146 showed apparent agglutination in the cytoplasm. ABSTRACT: Objectives: Bacterial strains that produce New Delhi metal-β-lactamase 1 (NDM-1) are a worldwide health threat. It remains a challenging task to find a potent NDM-1 inhibitor for clinical practice. Methods: Molecular docking and virtual screening of an in-house fungal natural product database for NDM-1 inhibitors were performed. Based on the screening results, the affinity and inhibition ability of potential NDM-1 inhibitors were determined using purified NDM-1. The efficacy of compounds in combination with four β-lactam antibiotics (meropenem, imipenem, ceftriaxone and ampicillin) was evaluated. Morphological changes in Klebsiella pneumoniae ATCC BAA-2146 after treatment with the compounds were visualised by transmission electron microscopy. Results: In silico screening led to the identification of four fungal products as potential NDM-1 inhibitors. Emerione A (1 ), a methylated polyketide with bicyclo[4.2.0]octene and 3, 6-dioxabicyclo[3.1.0]hexane functionalities, has significant activity in cells (Kd  = 11.8 ± 0.6 μM; IC50  = 12.1 ± 0.9 μM) and potentiates the activity of meropenem against two kinds of NDM-1-producing Enterobacteriaceae. To the best of our knowledge, emerione A (1 ) is the second fungal metabolite reported to exhibit NMD-1 inhibitory activity. According to the structural novelty of our database, we also found a new structural compound, asperfunolone A (2 ), with potential NMD-1 inhibitory activity. Conclusion: Considering the low toxicity of emerione A (1 ), it may represent a potential lead compound for anti-NDM-1 drug development.